Synthesis, crystal growth and characterizations of 4-fluorobenzyl ammonium dihydrogen phosphate of NLO single crystal [PFBADP]. (2022) - Manivannan, V.; Bhadhusha, N.; Gunasekaren, T.; Inmozhi, C.; Subash, M.; Uthrakumar, R.
Abstract: Good quality single crystal of p-fluorobenzyl ammonium dihydrogen phosphate [PFBADP], a compound has been successfully grown from aqueous solution by slow evaporation solution growth method. The crystal system and lattice parameters are confirmed by the single crystal X-Ray diffraction analysis. An optical absorption study on the sample shows that the material is well suitable for optical applications. The functional groups of the compound are confirmed qualitatively by FT-IR spectral analysis. The photoluminescence studies indicate that the grown crystals have a green fluorescence emission. Dielectric studies have been carried out for the grown crystal and the results were discussed in detail.